METODY ANALIZY EKONOMICZNEJ ZJAWISKA UBÓSTWA - Pollok, Artur (Wydział Prawa i Administracji UAM, 2002)
Poverty is one of the worst and most common oppressions that afflict humanity. This phenomenon occurs in any community, whether rich or poor. Wherever it affects more than a few individuals, it turns into a serious social problem. Social studies on poverty have been conducted for over a century (in Poland they were clearly intensified over the last decade). Despite its long history, the contemporary study is still unable to provide unambiguously a single definition of poverty or define its causes. This fact largely hinders both a close study of this phenomenon and an effective social policy against poverty and its results. The article attempts to summarize the results of the research done so far on the subject, in particular concerning the notion, typology, and changing perception of poverty. The article includes a proposed classification of poverty causes and a discussion of its main sources indicated by the contemporary study. Furthermore, the main poverty measurement methods have been discussed with an emphasis upon the problems involved and the practical implication of applying study results. Fighting poverty has been considered a priority of any country’s economic policy. According to the author, it is paramount to create a socially desirable goods and service division system that also promotes the production sphere as the source of universal prosperity.
METHODS OF ECONOMIC ANALYSIS OF POVERTY